Pengaruh 3A Terhadap Keputusan Berkunjung Wisatawan Pada Objek Wisata Air Terjun Temam - Natasha Dessy Putri Ramadhani; Rini Rini; Heri Setiawan (Politeknik Negeri Sriwijaya, 2021)
Brand awareness and brand image are very important in the business world, because they can invite and encourage consumers to buy and use the products or services offered by the company. This study analyzes these two factors in influencing the decision to purchase flight tickets in Palembang City. The sample in this study were 30 consumers who purchased flight tickets on Traveloka.com in Palembang during January 2020 - June 2020. The sampling technique used was non probability sampling with a purposive sampling approach. This study found that brand awareness has a significant effect on purchasing decisions, while brand image has no significant effect on purchasing decisions.